Capital, heterogeneous labour, global goods markets and unemployment - Albert G. Schweinberger (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2001)
A two country model of trade between a flexiwage and a minimum wage economy or two mmjmum wage economies is developed. The main novelty is that there are three factors of production: capital, skilled and unskilled labour. This unlocks the terms of trade. Unskilled labour is subject to the same or different minimum wages in one or both countries. The trading pattern of the two countries is explained in terms of differences in various factor intensities, endowments with the two fully employed factors (capital and skilled labour) and the binding minimum wage rates. Free trade may reduce the wage of the unskilled workers in the flexiwage economy and lower the unemployment in the minimum wage economy. This follows because unemployment may be a source of competitive advantage due to the income effect. If the two countries differ only in terms of factor endowments (but operate the same minimum wage) free trade moves the two countries towards an equalisation of unemployment.
Keywords: F11; J31; E24; 330; Minimum wages; global markets; unemployment